Plants against cancer: the immune-boosting herbal microbiome: not of the plant, but in the plant. Basic concepts, introduction, and future resource for vaccine adjuvant discovery - Mazzio, Elizabeth; Barnes, Andrew; Badisa, Ramesh; Council, Stevie; Soliman, Karam F. A. (Frontiers in Oncology, 2023)
Microorganisms (bacteria, fungi, archaea, algae, protozoa, viruses etc) shape innate and long-term acquired immunity in diverse natural living systems including plants and animals, the latter often exploited by vaccines and adjuvants, including tumor immunotherapies. All tumor vaccines work to reawaken, boost, and put into a state of pro-inflammation the immune system to overpower the immunosuppressive barrier circumscribing malignancy responsible for loss of host recognition. This review covers the historical use of microbes as anti-genic epitopes to treat cancers, from the late 1800s (e.g., Busch,Coley,Fehleisen) where spontaneous remission was observed in cancer patients after contraction of an “acute” “febrile 38-40 °C,” infection (streptococcus pyrogens) with the first immunotherapy to today’s modern tumor immune therapies. We discuss the opposing deleterious immune suppressive forces arising from suppressive chemotherapies, pain killers and antibiotics. This background serves as a backdrop to introduce a fairly new concept pertaining to plant medicine, constituting the “edible immune activating microbiome”, which is not of the plant/ nor its phytochemicals but a uniquely separate component. While humans have consumed plant medicines for thousands of years (along with bugs), only few have examined/reported/suggested that the “immune boosting” capacity of specific herbs could have little to do with the plant, and largely attributable to concentrated inactivated foreign antigenic microbial associated molecular pattern (MAMPs) debris. These are the same MAMPS arising from killed, heat-inactivated, or antigen epitope subunits + adjuvants are used in vaccines. Plant microbiomes while reported in the fields of ecology, crop science, food science or as live (not dead) communities in foods, are reported without application to human immune response. Concentrated acid/thermally stabile MAMPS in specific herbs would provide structural motifs to cognate pattern recognition receptors (PPRs) in the upper gut-associated lymphoid tissue (GALT)/Peyer’s patches and lamina propria which shape our innate and acquired immune systems. Given PPR agonists in vaccines can boost antibody titers, CD8+ and CD4+ T cells, NK activity, hematopoiesis, M2 to M1 macrophage phenotype transition etc., the world of plant medicine needs to re-examine the accrued dead microbiome as a separate component to plant medicine, unrelated to the plant/ phytochemicals but pertaining to immune boosting effects.